Knowledge and needs for prevention and management of sports injury among high/vocational school students in Taiwan - Wang, K. M.; Huang, Y. C. (International Journal of Sport & Health Science, 2006)
Analysis and recommendations of knowledge and needs for "Prevention and Management of Sports Injury" on high/vocational school students, will serve as a reference in teaching material selection and lecturing method for teachers in relating subject, so as to achieve effective teaching which also fulfills the needs of students. The purpose of this study was to investigate the current level of knowledge and needs for "Prevention and Management of Sports Injury" among 1,649 high/vocational school students. The main results from the analysis are: Knowledge for Prevention and Management of Sports Injury has statistically significant in gender, type of school, education system, grade and source of knowledge. Needs for Prevention and Management of Sports Injury has statistically significant in only gender and source of knowledge. The entire study population considered training for "Prevention and Management of Sports Injury" highly needed indicating students who were more acquainted with "Prevention and Management of Sports Injury" had higher needs for more knowledge.